Parents of disabled children. The educational system and the everyday challenges - Hadjiyiannakou, Anastasia; Ioannou, Christina; Tziogkouros, Charalambos (International Journal about Parents in Education, 2023)
The purpose of this presentation is to present how parents with disabled children view and understand the existence of their disabled children through the lens of special education professionals and also how professionals experienced and are affected from this understanding. After a lot of discussions and also after the completion of a questionnaire it had been discovered that parents of disabled children seemed to be a great issue for the professionals who work with their disabled children in case of Cyprus. Thus the Ministry of Education and Culture decided to organize a program which its aim will be to evaluate the difficulties that the professionals faced and secondly it will provide them with the right skills in order to make them able and ready to come across those difficulties. This program consisted of two meetings during the school year 2005-2006 and six meetings during 2006-2007. Parents of disabled children seemed to be a big issue to professionals, since their behaviour sometimes caused lot of difficulties in the everyday life of a school.  The group of professionals was made of 22 “special” education teachers who work in the Ministry of Education and Culture. The group was closed for everyone else apart from the two educational psychologists who were responsible for the program and the representative of the Special Education Department. All the information that was mentioned in those groups could not be shared or discussed anywhere else apart from the specific group. It was decided from the organizing team as well that those meetings must be held in places other than school places, since this will provide the participants the chance to talk freely in a much different environment than their everyday environment at work. The analysis on the results is based on qualitative methods, since the group of professionals acts as a focus group.